Ionic Liquids for Propene-Propane Separation - Mokrushin, Vladimir; Assenbaum, Daniel; Paape, Natalia; Gerhard, Dirk; Mokrushina, Liudmila; Wasserscheid, Peter; Arlt, Wolfgang; Kistenmacher, Hans; Neuendonf, Stephanie; Göke, Volker (Chemical Engineering & Technology, 2010)
This paper presents an extensive study on the feasibility of ionic liquids (IL) for the extractive distillation of propene-propane mixtures. A new experimental method for express screening of non-volatile entrainers was elaborated. A series of ILs and their mixtures were screened at ambient temperature and low pressures. The screening results show that every tested IL turns a low boiler propene into a high boiler and the alkene-to-alkane separation factor can be as low as 0.28. The solubility and separation efficiency can be tuned by adjusting the chemical structures of the ions forming the IL. It was found that shortening of the alkyl substituents of the imidazolium ions leads to a decrease in capacity and to an increase in the separation factor. Interestingly, ILs containing nitrile functionalities in either the cation or the anion showed, in our experiments, enhanced separation ability combined with still good capacities. From our thermodynamic measurements, [EMIM] [ [B(CN)(4)] was proved to be the most promising candidate. Binary mixtures of ILs were also tested and resulted in separation factors and capacities between the values for the individual ILs. For the most promising candidates, also autoclave measurements at elevated temperatures and pressures were carried out. These experiments indicate that the separation ability decreases with growing temperature and loading. In general, our study definitely proves the high potential of ILs to act as entrainers in the extractive distillation of propene-propane mixtures or for the separation of any other low-boiling alkene-alkane mixture.
Keywords: Express screening experiments; Extractive distillation; Headspace chromatography; Ionic liquids; Propene - propane mixtures